LA THÉORIE TRADITIONNELLE DE LA PROTECTION DIPLOMATIQUE DES INDIVIDUS EN DROIT INTERNATIONAL ET LA PERSPECTIVE DU DROIT DE L’UNION EUROPEENNE - Fragola, Massimo (European Scientific Journal, ESJ, 2014)
Diplomatic protection consists of the invocation by a State of the responsibility of another State for an injury caused by an internationally wrongful act of that State to a natural or legal person that is a national of the former State with a view to the implementation of such responsibility. In this case, the State acts on its own behalf, to protect its rights, on an international level and through diplomatic action or other means of peaceful settlement conducted by diplomatic officials or Government representatives. In the Maastricht Treaty was established the "Citizenship of the European Union", which defined rights and duties for all citizens holding the nationality of a Member States. Among the various provisions which set forth these rights states that every citizen of the Union shall, in the territory of a third country in which the Member State of which he is a national is not represented, be entitled to protection by the diplomatic or consular authorities of any Member State, on the same conditions as the nationals of that State.